Legal protectionism of the commercial agency in Colombia versus economic integration treaties - Isabel C. García Velasco (Cuadernos de Administración, 2011)
The business world tends to establish a set of uniform norms for international trade. It works on forms of contracting that produce local and international benefits for commercialization (products, goods, and services); this has been understood by commerce and the law. Nonetheless, there are many obstacles (fiscal, taxes, legal protection of some contractual practices, and limiting clauses, among others) and it is sought for these to disappear, especially those that imply exaggerated protection of national commerce. The States seek mechanisms that help them regulate their relations among the different players and treaties are the main source from which emerge mandates that affect national and world economies, facilitating the creation of companies to explore new market places. It is thus that in the trade treaties or agreements, the objective is for trade to flow freely and for the nations to benefit from commercial exchange. In the private laws of the different nations, there are legal institutions that due to their national protection hinder their application at the international level, as is the case of the commercial agency, a controversial contract since its beginnings, recognizing that it has been an alternative for doing business in Colombia. This article critically analyzes the legal framework of the contract of commercial agency versus the integrationist objectives in free trade agreement (FTA) negotiations that tend to seek flexibility in this contractual form, according to the conditions imposed by the United States of modifying some contract benefits in the Colombian legislation. The aforementioned leads to ponder if with the modifications the Colombian State agreed to, within the framework of the Free Trade Agreement negotiations, the figure of this contract will continue being attractive, as a way of creating commercial representation companies in Colombia